2008
DOI: 10.4103/1596-3519.55657
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana smoking among secondary school students in Zaria, Nigeria: Factors responsible and effects on academic performance

Abstract: Background:The use of Marijuana is on the increase worldwide especially among adolescents and youths. Marijuana smoking has gained a foothold in our environment because of peer group influence, accessibility and availability. Its medico-social effects could ruin the life and future of our youths. This study was undertaken to determine the prevalence and the factors that influence secondary school students in Zaria LGA to smoke and the effects on academic performance. Methods: A cross-sectional descriptive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
4
15
2
Order By: Relevance
“…For instance, they noted while 1.0% of 11 year olds had used cannabis in the last year, about 31.0% of 15 year olds had done so. Local studies have also shown similar trends in cannabis use among adolescent students (Shehu & Idris, 2008;Igwe et al, 2009). This trend has also been observed with alcohol use (Makanjuola et al, 2007;Gureje et al, Downloaded by [New York University] at 15:25 02 July 2015 2007).…”
Section: Discussionsupporting
confidence: 53%
“…For instance, they noted while 1.0% of 11 year olds had used cannabis in the last year, about 31.0% of 15 year olds had done so. Local studies have also shown similar trends in cannabis use among adolescent students (Shehu & Idris, 2008;Igwe et al, 2009). This trend has also been observed with alcohol use (Makanjuola et al, 2007;Gureje et al, Downloaded by [New York University] at 15:25 02 July 2015 2007).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, while several Nigerian studies have described parental and friends 0 influence on adolescent substance use [8][9][10][11][12][13][14][15][16][17][18][19][20][21], few have investigated personal risk factors (e.g. knowledge, attitudes, and beliefs) and none have investigated risk perceptions and skills.…”
Section: Introductionmentioning
confidence: 99%
“…knowledge, attitudes, and beliefs) and none have investigated risk perceptions and skills. To date, most studies on personal risk factors have focused on cigarette smoking [13][14][15][16][17][18][19][21][22][23][24] but very few have investigated correlates of alcohol [25][26][27] and illicit drugs use [20,26,28]. Since all these factors can be related to the risk of initiation and can be modified by specific prevention interventions, it is important to identify which areas deserve health promotion interventions targeting adolescents in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of marijuana smoking among Nigerian youth is about 9.4% [23] while the prevalence in the entire population is 5.0% [22]. However, the prevalence of Marijuana smoking among adults in Nigeria varies from one location to another.…”
Section: Estimation Of Parametersmentioning
confidence: 99%
“…However, the prevalence of Marijuana smoking among adults in Nigeria varies from one location to another. The prevalence could be as high as 26% in places like Port-Harcourt , Rivers state [23]; it may be as low as 5% in places like Ilorin, Kwara state [22]; while it is relatively moderate in places like Zaria, Kaduna state with a prevalence rate of 9.4% [23]. Here, we assume that the prevalence of Marijuana smoking among Nigerian adults is about 10%.…”
Section: Estimation Of Parametersmentioning
confidence: 99%